2014 36th Annual International Conference of the IEEE Engineering in Medicine and Biology Society 2014
DOI: 10.1109/embc.2014.6943730
|View full text |Cite
|
Sign up to set email alerts
|

Design and clinical feasibility of personal wearable monitor for measurement of activity and environmental exposure

Abstract: Human exposure to specific environmental factors (e.g. air quality, lighting, and sound) is known to play an important role in the pathogenesis of many chronic diseases (e.g. asthma) and mental health disorders (e.g. anxiety). However, conventional fixed environmental monitoring stations are sparsely located and, despite environmental models, cannot adequately assess individual exposure levels. New forms of low-cost portable monitors have begun to emerge that enable the collection of higher spatial density “cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 9 publications
(8 reference statements)
0
21
0
Order By: Relevance
“…Among those proposed, this review focused on the following pollutants: nitrogen dioxide (NO 2 ), ozone (O 3 ), carbon monoxide (CO), volatile organic compounds (VOCs) and airborne particulate matter (PM) with an aerodynamic diameter below 2.5 µm (PM 2.5 ) and below 10 µm (PM 10 ) (the coding “PM” was applied to categorize NGMSs that can simultaneously analyze more than one fraction of particulate matter) ( Table 2 ). After the full-text reading step, it was outlined that some pollutants were poorly investigated and the available evidence did not allow for an extensive discussion: for this reason, NGMSs for NO [ 25 , 27 , 28 , 29 , 30 , 31 ], NO x [ 32 , 33 ], CO 2 [ 31 , 34 , 35 , 36 ], SO 2 [ 37 , 38 ], and BC [ 39 ] were not discussed in this review. As a first result, we found that the most commonly used sensors to monitor the selected air pollutant gases are those produced by Alphasense ( ; accessed on 22 April 2021; Great Notley, Essex, UK).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among those proposed, this review focused on the following pollutants: nitrogen dioxide (NO 2 ), ozone (O 3 ), carbon monoxide (CO), volatile organic compounds (VOCs) and airborne particulate matter (PM) with an aerodynamic diameter below 2.5 µm (PM 2.5 ) and below 10 µm (PM 10 ) (the coding “PM” was applied to categorize NGMSs that can simultaneously analyze more than one fraction of particulate matter) ( Table 2 ). After the full-text reading step, it was outlined that some pollutants were poorly investigated and the available evidence did not allow for an extensive discussion: for this reason, NGMSs for NO [ 25 , 27 , 28 , 29 , 30 , 31 ], NO x [ 32 , 33 ], CO 2 [ 31 , 34 , 35 , 36 ], SO 2 [ 37 , 38 ], and BC [ 39 ] were not discussed in this review. As a first result, we found that the most commonly used sensors to monitor the selected air pollutant gases are those produced by Alphasense ( ; accessed on 22 April 2021; Great Notley, Essex, UK).…”
Section: Resultsmentioning
confidence: 99%
“…It allows easy and stable communication between NGSMs and a smartphone in which the mobile app is supported. In this review, 23 articles [ 19 , 27 , 32 , 35 , 37 , 38 , 39 , 50 , 51 , 56 , 60 , 67 , 69 , 77 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ] out of 67 reports information about the use of any mobile app supporting NGMSs; most of those (13 apps) were developed on the Android platform [ 6 , 35 , 37 , 38 , 40 , 50 , 53 , 60 , 81 , 84 , 86 , 87 , 88 ], only one was developed on the iOS platform [ 81 ], and the remaining were not specified. As reported by Kanjo et al [ 89 ], using a mobile phone to collect data can bring many advantages, especially related to the fact that (i) a large percentage of the population carries around mobile phones; (ii) many kinds of data can be processed, stored, and transferred easily by mobile phones; (iii) the collection of data should be more power-efficient because the acquired information are sent directly to the mobile phone.…”
Section: Resultsmentioning
confidence: 99%
“…In other studies where the daysimiter is not considered, the scope of the research are different: in [ 68 ], a miniaturised microclimate station, specifically tailored to be worn while walking or cycling and therefore collecting data according to the pedestrian perspective in anthropogenic areas, was used to collect data on illuminance levels and some other variables related to thermal and air quality EFs; in [ 69 ], a calibrated wearable device, called Eco-Mini, used for environmental monitoring is presented; in [ 70 ], the authors showed how a textile composed of Janus chromic fibers shows stable practical performance and excellent sensitivity to UV/IR radiation to achieve real-time, energy-free, visual monitoring of IR radiation temperature and UV index; finally, in [ 71 ], the authors presented a fully low-cost and open-source (in accordance with the requirements defined by UNICEF, see Section 1.1 ) wearable light data logger for studying physiological and psychological effects of light.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…To the best of our knowledge, there are 2 prototypes presented by Massachusetts Institute of Technology(MIT, USA) and Rostock University (Center for Life Science Automation, Germany) that measure both sound levels and hazardous gases, each with its own features and specifications. Fletcher et al [49] presented a waist-worn device with capability of measuring two hazardous gases, sound level monitoring and physical ambient parameters (air temperature and humidity). This device (called Eco-mini) does not support real-time data monitoring and can only store the data in a SD external memory.…”
Section: Related Workmentioning
confidence: 99%